Identity and Language of Education in the Kurdistan Region (Raparin Journal of Humanities (RJH), 2022)
This research is intended to shed light on the problems of the Kurdish language in the Kurdistan Region, especially in the field of education and higher education. This is because we assume that in modern life, there is a great risk which threatens our cultural identity in the light of globalization that tries to weaken our natural identity and impose a unipolar cultural dominance of the English language. If in the past the responsibility lies with the enemies of the Kurdish people in crackling down on the kurdish language in the stages of the occupation, the responsibility now lies with the officials of the Kurdistan regional Government (from the Ministry of Education and the Ministry of Higher Education). Because they do not have a policy and plan related to the language, and do not put an end to the disregard of the Kurdish language and the violation of the state law and constitution. In this regard, we have tried to present different views on the language of education in the centers of education and its effects on the linguistic identity of the individual and Kurdish society. In addition, schools and education centers were classified according to languages. Finally, the importance and status of language in the process of education were analyzed in order to reach conclusions on the formulation of a current plan of the Kurdish language in the education process.